Retracted: A hybrid feature selection algorithm for microarray data - Zheng, Yuefeng; Li, Ying; Wang, Gang; Chen, Yupeng; Xu, Qian; Fan, Jiahao; Cui, Xueting (Concurrency and computation, 2019)
Retraction: Zheng Y, Li Y, Wang G, et al. A hybrid feature selection algorithm for microarray data. Concurrency Computat Pract Exper. 2018;e4716. https://doi.org/10.1002/cpe.4716. The above article, published online on 25th October 2018 in Wiley Online Library (wileyonlinelibrary.com), has been retracted by agreement between the authors, the journal Editor in Chief Professor Geoffrey Fox, and John Wiley and Sons Ltd. The retraction has been agreed as an alternative algorithm was used than that described in the manuscript resulting in foundational errors that are beyond the application of errata.